In-Vitro Susceptibility of Fluoroquinolone Resistance Escherichia Coli to Alkaloid Extracted from Phyllanthusniruri (Global Journal of Medical Research, 2013)
The antibacterial potency of alkaloid extracted from Phyllanthus niruri was examined on Fluoroquinolone resistant Escherichia coli isolated from different clinical samples using disk diffusion method. Different concentrations (0.1 -5mg/ml) of the alkaloid were used. It was observed that at 0.5mg/ml the extract showed more potency on Escherichia coli isolated from urine than from other samples with a diameter of zone of inhibition of 25.5mm. The percentage susceptibility of the isolated bacterium from urine, blood, semen, swab, and high vagina swab (HVS) to the alkaloid were 75%, 75%, 100%, 60% and 60% respectively. Thirty-seven (37) strains were tested for extended-spectrum beta-lactamase (ESBL) identification. They were all positive for blaCTX-M in 37(100%) of the ESBL-carrying strains. CXT-M-14 was the most frequently isolated ESBL (n=15), followed by CTX-M-27 (n=12) and CTX-M-15(n=5), one strain (CEC7) was carrying both blaCTX-M-14and blaCTX-M-15. Strain CEC14 was carrying a blaCTX-M-14 variant, which differed from the parental enzyme by a single transversion. Using PCR amplification,4 clusters containing 9, 8, 3, and 2 strains were identified. Pulsed-field gel electrophoresis of FQ-resistant E.coli identified clonal spread of 1(one) strain among 18 patients. It was concluded that all the bacterium resistant to fluoroquinolone were susceptible to the alkaloid extract.
Keywords: In-vitro; fluoroquinolone; escherichia coli; alkaloid; phyllanthus niruri